Readability Level of English Reading Text Used In The Era of Pandemic - Maru, Mister Gidion; Paranduk, Rida; Tuerah, Javier (Syntax Literate, 2021)
This study attempts to investigate the readability level of the text used in the Junior High School. Taking the material from those read in the two prominent schools; public and private school. Being measured by the given formula and then followed by the given test to students, this study reveals that the readability level of four reading texts as the source of the data in this study indicates various level. It is only one out of four texts that was appropriate for 9th grade students. This affects the students’ purpose of reading competencies of the students in private Junior school who have tendency toward unassisted reading than the students in the public school. It implies the number of students who need the instruction or need assisted in reading. The students within this school demand more instruction than those in private school. The similar condition shown in the students who categorized in the frustration level. As the consequences, this circumstance requires teacher’s serious intervention among others by cautiously doing text selection and adjusting teaching strategy to students’ reading level competency.